Nabi Muhammad dan Reformasi Masyarakat Arab - Haris, Ahmad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
For Muslims in particular, the life of the Prophet Muhammad (571-632) has been unlimited sources of inspiration, one of which is how he was successfully reforming the sixth and seventh century Arab society. In Mecca, he was able to transfonn the paganistic Arabs into a monotheistic society furnished with new morality. In Medina, he completed his mission by constructing a nau pluralistic society under the banner of Islam. This Medinan society (masyarakat madani) could becorne a model for reconstructing other societies such as the Indonesian Muslims.